The proposed need for integrated maternal and child oral health policy: A case of South Africa - Ramphoma, Khabiso; Rampersad, Nashna; Singh, Nuerisha; Mukhari-Baloyi, Ntsakisi; Naidoo, Sudeshni (Frontiers in Oral Health, 2022)
The high oral disease burden among children in South Africa, specifically early childhood caries, has received scant attention despite the fact that it is a public health concern that negatively impacts the overall well-being and quality of life of the child. While South Africa has a number of well documented policies that focus on oral health in general and maternal and prenatal health, none specifically addresses the oral health of children under the age of six years. The integration of oral health in maternal and child health care in South Africa could lead to an improved oral health quality of life and better oral health outcomes for mothers and children to address the high prevalence of childhood caries and unmet treatment needs for this population. While the integration of oral health care into primary healthcare is recognised as crucial and affordable, it however continues to be neglected. In South Africa, oral health disparities are attributed to the unequal distribution of oral health services, and policies that govern oral, maternal and child health seem to work in parallel with one another. Integrating oral health into interventions for primary health care delivery is a cost-effective way to improve the health of disadvantaged groups. Considering that maternal oral health predicts children's oral health and primary health care teams regularly see under-6-year-olds, this primary care setting is ideal for integration of these services. Despite growing interest in an integrated oral health and primary care system, there is little literature on oral health integration models. Improving the oral health of vulnerable populations requires integrating oral health into primary care and implementing interdisciplinary public health programs. The development of an Integrated Maternal and Child Oral Health policy would play a critical role in advancing integration; however, such a policy should be designed with both implementation and translation in mind for it to be successfully followed through. Such a policy should be comprehensive and contextual, aimed at increasing access to oral health services for women and children and reduce the oral disease burden. This paper proposes and describes the possible content and objectives of such a policy that will enhance effective leadership and accountability and strengthen health system delivery platforms for quality maternal and child oral health services along the continuum of healthcare. Furthermore, it will illustrate the importance of a policy that aims to promote coordinated, relevant, trans-multi-disciplinary and inter-sectoral community engagement to improve pregnancy and oral health outcomes, and importantly, establish a sustainable and contextual surveillance system for maternal and child oral health.